A quantum dot enhanced long afterglow synergistic photocatalytic material and preparation method thereof

By introducing the collaborative use of quantum dots and long afterglow materials into the photocatalytic materials, the problem of degradation of catalytic performance when the light environment is weak is solved, and the catalytic stability and fluorescence ability of the material are improved.

CN119771472APending Publication Date: 2025-04-08WUYANG AOKAI MEDICAL TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510043265.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-10
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

When the light environment is weak, the catalytic performance of the photocatalytic material is reduced, and the coordinated use of long afterglow materials and photocatalytic materials have interface uncertainty and competition for photogenerated carriers, resulting in a decrease in fluorescence capability and catalytic stability.

Method used

By introducing quantum dots to the interface of long afterglow materials and annealing and recombining with photocatalytic materials, the quantum dots act as a new center for photogenerating electrons and holes, extend the lifetime of photogenerated electrons and holes, and improve the material's light absorption performance and interface effect.

Benefits of technology

A composite material with stable catalytic activity and strong fluorescence ability can continue photocatalyzing in dark environments and enhance photocatalytic activity in bright environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The present invention provides a quantum dot enhanced long afterglow synergistic photocatalytic material and a preparation method thereof, which belongs to the field of photocatalytic semiconductor technology, and comprises the following raw materials: fluorescent component I and photocatalytic material component II; the fluorescent component I comprises the following raw materials in parts by weight: 1-2 parts of citric acid or ammonium citrate, 2-3 parts of strontium aluminate, 2-3 parts of strontium silicate, 2-3 parts of sodium tungstate, 2-3 parts of bismuth nitrate, 2-3 parts of cuprous sulfide, 10-25 parts of water, and 40-45 parts of ethylene glycol; the photocatalytic material component II comprises the following raw materials in parts by weight: 2-3 parts of urea, 2-3 parts of ammonium sulfate, 2-3 parts of melamine, 2-4 parts of dicyandiamide, 2-3 parts of cyanuric acid, 2-3 parts of nano titanium dioxide, 2-3 parts of zinc oxide, and 10-15 parts of water and a preparation method thereof. The present invention provides a quantum dot enhanced long afterglow synergistic photocatalytic material and a preparation method thereof, and realizes obtaining a composite material with stable catalytic activity and strong fluorescence ability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of photocatalytic semiconductors, and in particular to a quantum dot enhanced long afterglow synergistic photocatalytic material and a preparation method thereof. Background Art

[0002] As a new environmentally friendly technology, semiconductor photocatalysis technology has many advantages in degrading pollutants, such as: non-selective degradation, no secondary pollution; can reduce energy and raw material consumption; photocatalysts are cheap, non-toxic, stable, and reusable. Therefore, photocatalytic semiconductors have been widely used in environmental governance. However, some problems also arise in this application process. When the light environment is weak, the high dependence of photocatalytic materials on light sources will not only reduce the photocatalytic performance, but also increase the subsequent maintenance costs.

[0003] Long afterglow luminescent material is also called luminous material. It is a photoluminescent material that emits visible light when excited by a light source and stores part of the light energy. After the excitation stops, it slowly releases the energy in the form of light. Although there have been a few reports on the coordinated use of long afterglow materials and photocatalytic materials, the diversity of the properties of the long afterglow materials themselves affects the uncertainty of the interface between the long afterglow materials and the photocatalytic materials, and even due to the competitive recombination of photogenerated carriers, it will deteriorate the fluorescence ability and photocatalytic ability or reduce the catalytic stability of the material. Summary of the invention

[0004] In view of this, the present invention provides a quantum dot enhanced long afterglow synergistic photocatalytic material and a preparation method thereof, so as to obtain a composite material with stable catalytic activity and strong fluorescence ability.

[0005] To achieve the above object, the present invention provides a method for preparing a quantum dot enhanced long afterglow synergistic photocatalytic material, comprising the following steps: S1. Dissolve bismuth nitrate in ethylene glycol, add strontium aluminate and strontium silicate in sequence, disperse evenly to obtain a quantum dot solution, and stir; dissolve citric acid or ammonium citrate in water, add sodium tungstate and cuprous sulfide in sequence, disperse evenly, and stir to obtain a suspension; slowly add the suspension to the vigorously stirred quantum dot solution, stir to obtain a solution A; keep the solution A warm, cool, filter, wash, and dry to obtain a product A; S2. The urea, ammonium sulfate and cyanuric acid are dissolved in water, and dicyandiamide and melamine are added, and the mixture is evenly dispersed to obtain a solution B, and the water in the solution B is evaporated to obtain a solid, and the solid is annealed and sintered to obtain a product B; S3. Grind the nano-titanium dioxide, zinc oxide, the product A and the product B evenly, perform secondary annealing and sintering, and grind again into powder to obtain a composite material, namely, a quantum dot enhanced long afterglow synergistic photocatalytic material.

[0006] Optionally, the stirring time in S1 is 0.5-2h, the stirring speed is 500-700rpm; the intense stirring speed is 1000-1200rpm.

[0007] Optionally, the insulation condition of the solution A is a temperature of 180-200° C. for a insulation time of 24-26 hours; after insulation, the solution A is cooled to room temperature and filtered, and the washing method after filtration is to wash alternately with water and ethanol for 2-3 times.

[0008] Optionally, the temperature at which the water of the solution B evaporates is 65-85°C.

[0009] Optionally, the solid annealing conditions are a temperature of 550-600° C. and a time of 2-3 h; the solid annealing uses a muffle furnace.

[0010] Optionally, the grinding time is greater than 0.5 h, and the grinding includes manual grinding and mechanical grinding.

[0011] Optionally, the uniform dispersion is achieved by using ultrasonic dispersion.

[0012] Optionally, the bismuth nitrate and sodium tungstate are hydrates.

[0013] Optionally, the strontium aluminate and strontium silicate are sieved through a 300-mesh sieve.

[0014] In order to achieve the above object, the present invention also provides a quantum dot enhanced long afterglow synergistic photocatalytic material, comprising the following raw materials: fluorescent component I and photocatalytic material component II; The fluorescent component I comprises the following raw materials in parts by weight: 1-2 parts of citric acid or ammonium citrate, 2-3 parts of strontium aluminate, 2-3 parts of strontium silicate, 2-3 parts of sodium tungstate, 2-3 parts of bismuth nitrate, 2-3 parts of cuprous sulfide, 10-25 parts of water, and 40-45 parts of ethylene glycol; The photocatalytic material component II comprises the following raw materials in parts by weight: 2-3 parts of urea, 2-3 parts of ammonium sulfate, 2-3 parts of melamine, 2-4 parts of dicyandiamide, 2-3 parts of cyanuric acid, 2-3 parts of nano titanium dioxide, 2-3 parts of zinc oxide and 10-15 parts of water.

[0015] The above technical solution of the present invention includes at least the following beneficial effects: The technical solution provided by the present invention adopts quantum dots that are introduced into the interface of the long afterglow material and are compounded with the photocatalytic material through annealing. The quantum dots can serve as new recombination centers for photogenerated electrons and holes, greatly extending the lifespan of photogenerated electrons and holes. In addition, the inherent high light absorption performance characteristics of quantum dots can greatly improve the light absorption performance of the material. At the same time, the small-sized and easily dispersed quantum dots also improve the interface effect of different materials, thereby improving the catalytic stability of the overall material. The large-sized long afterglow material can not only serve as an excellent carrier for dispersing photocatalytic materials, but the fluorescence emitted by the long afterglow material after absorbing light can serve as an auxiliary light source for the photocatalytic material, which not only gives the photocatalytic material a longer lifespan of photogenerated free radicals in a dark environment, but also enhances the catalytic activity of the photocatalytic material in a bright environment. DETAILED DESCRIPTION In order to make the purpose, technical solution and advantages of the embodiment of the present invention clearer, the technical solution of the embodiment of the present invention will be clearly and completely described in combination with the embodiment of the present invention. Obviously, the described embodiment is a part of the embodiment of the present invention, not all the embodiments. Based on the described embodiment of the present invention, all other embodiments obtained by ordinary technicians in this field belong to the scope of protection of the present invention.

[0016] Example 1 Take the following raw materials in parts by weight: 2 parts of ammonium citrate, 3 parts of strontium aluminate, 3 parts of strontium silicate, 2 parts of sodium tungstate, 2 parts of bismuth nitrate, 3 parts of cuprous sulfide, 35 parts of water, 45 parts of ethylene glycol; 2 parts of urea, 2 parts of ammonium sulfate, 2 parts of melamine, 2 parts of dicyandiamide, 2 parts of cyanuric acid, 2 parts of nano titanium dioxide, 2 parts of zinc oxide, bismuth nitrate and sodium tungstate are hydrates, and strontium aluminate and strontium silicate are sieved through a 300-mesh sieve.

[0017] S1. Dissolve bismuth nitrate in ethylene glycol, add strontium aluminate and strontium silicate in turn, disperse evenly by ultrasonication to obtain a quantum dot solution, and stir at 500 rpm for 1 hour; dissolve ammonium citrate in 20 parts of water, add sodium tungstate and cuprous sulfide in turn, disperse evenly, and stir at 600 rpm for 0.5 hour to obtain a suspension; add the quantum dot solution stirred vigorously at 1000 rpm to the suspension for 40 minutes, and stir at 700 rpm for 2 hours to obtain solution A; keep solution A at 180°C in a polytetrafluoroethylene reactor for 24 hours, then cool to room temperature, filter, wash twice with water and ethanol alternately, and dry to obtain product A; S2. Dissolve urea, ammonium sulfate and cyanuric acid in 15 parts of water, add dicyandiamide and melamine, and disperse them evenly to obtain solution B. After evaporating the water of solution B at 65°C, a solid is obtained. The solid is placed in a muffle furnace and annealed at 550°C for 3 hours to obtain product B. S3. Grind the nano-titanium dioxide, zinc oxide, product A and product B evenly with ball mill, anneal and sinter for a second time at 600°C in a muffle furnace for 2h, and grind again with ball mill into powder to obtain a composite material, i.e., a quantum dot enhanced long afterglow synergistic photocatalytic material.

[0018] Example 2 Take the following raw materials in parts by weight: 1 part citric acid, 2 parts strontium aluminate, 2 parts strontium silicate, 3 parts sodium tungstate, 3 parts bismuth nitrate, 3 parts cuprous sulfide, 30 parts water, 40 parts ethylene glycol; 3 parts urea, 3 parts ammonium sulfate, 3 parts melamine, 4 parts dicyandiamide, 3 parts cyanuric acid, 3 parts nano titanium dioxide, and 3 parts zinc oxide.

[0019] S1. Dissolve bismuth nitrate in ethylene glycol, add strontium aluminate and strontium silicate in turn, disperse evenly by ultrasonication to obtain a quantum dot solution, and stir at 700 rpm for 1.5 hours; dissolve citric acid in 15 parts of water, add sodium tungstate and cuprous sulfide in turn, disperse evenly, and stir at 500 rpm for 1 hour to obtain a suspension; add the quantum dot solution stirred vigorously at 1200 rpm to the suspension for 45 minutes, and stir continuously at 700 rpm for 1.5 hours to obtain solution A; keep solution A at 200°C in a polytetrafluoroethylene reactor for 26 hours, then cool to room temperature, filter, wash with water and ethanol alternately for 3 times, and dry to obtain product A; S2. Dissolve urea, ammonium sulfate and cyanuric acid in 15 parts of water, add dicyandiamide and melamine, and disperse them evenly to obtain solution B. After evaporating the water of solution B at 85°C, a solid is obtained. The solid is annealed and sintered at 600°C in a muffle furnace for 2 hours to obtain product B. S3. Grind the nano-titanium dioxide, zinc oxide, product A and product B evenly by hand, perform secondary annealing and sintering at 550°C for 3h in a muffle furnace, and grind them into powder again by hand to obtain a composite material, namely, a quantum dot enhanced long afterglow synergistic photocatalytic material.

[0020] Example 3 The difference from Example 2 is that the following raw materials are used: 1 part citric acid, 2 parts strontium aluminate, 2 parts strontium silicate, 2 parts sodium tungstate, 2 parts bismuth nitrate, 2 parts cuprous sulfide, 30 parts water, 40 parts ethylene glycol; 2 parts urea, 2 parts ammonium sulfate, 2 parts melamine, 2 parts dicyandiamide, 2 parts cyanuric acid, 2 parts nano titanium dioxide, 2 parts zinc oxide. The remaining steps and operations are consistent with Example 1.

[0021] Example 4 The only difference from Example 2 is that the following raw materials are used: 2 parts of citric acid, 3 parts of strontium aluminate, 3 parts of strontium silicate, 3 parts of sodium tungstate, 3 parts of bismuth nitrate, 3 parts of cuprous sulfide, 35 parts of water, 45 parts of ethylene glycol; 3 parts of urea, 3 parts of ammonium sulfate, 3 parts of melamine, 4 parts of dicyandiamide, 3 parts of cyanuric acid, 3 parts of nano titanium dioxide, and 3 parts of zinc oxide. The remaining steps and operations are consistent with those of Example 1.

[0022] Comparative Example 1 Compared with Example 2, the only difference is that bismuth nitrate is not added to the raw materials, and the remaining steps and operations are consistent with Example 1.

[0023] Comparative Example 2 Compared with Example 2, the only difference is that cuprous sulfide is not added to the raw materials, and the remaining steps and operations are consistent with Example 1.

[0024] Comparative Example 3 Compared with Example 2, the only difference is that strontium aluminate and strontium silicate are not added to the raw materials, and the remaining steps and operations are consistent with Example 1.

[0025] Comparative Example 4 Compared with Example 2, the only difference is that strontium aluminate and strontium silicate are not added to the raw materials, and the remaining steps and operations are consistent with Example 1.

[0026] Comparative Example 5 Compared with Example 2, the only difference is that urea is not added to the raw materials, and the remaining steps and operations are consistent with Example 1.

[0027] Comparative Example 6 Compared with Example 2, the only difference is that nano titanium dioxide and zinc oxide are not added to the raw materials, and the remaining steps and operations are consistent with Example 1.

[0028] Comparative Example 7 Compared with Example 2, the only difference is that melamine and cyanuric acid are not added to the raw materials, and the remaining steps and operations are consistent with Example 1.

[0029] Comparative Example 8 Compared with Example 2, the only difference is that ethylene glycol in the raw material is replaced with an equal volume of water, and the remaining steps and operations are consistent with Example 1.

[0030] Comparative Example 9 Compared with Example 2, the only difference is that ammonium sulfate is not added to the raw materials, and the remaining steps and operations are consistent with Example 1.

[0031] The composite materials obtained in the above Examples 1 to 4 and Comparative Examples 1 to 9 were respectively subjected to photocatalytic degradation of NO, AMHT photocatalytic degradation of formaldehyde, degradation of tetracycline and degradation of organic dyes: Photocatalytic degradation of NO: The NO degradation reaction was carried out in a sealed 2.5 L stainless steel rectangular reactor, the upper surface of which was made of quartz glass. A long arc xenon lamp (500 W) with a cutoff filter (λ>420 nm) was used as the light source. 0.2 g of quantum dot enhanced long afterglow synergistic photocatalytic material was evenly distributed at the bottom of the reactor, and NO from a compressed gas cylinder was continuously introduced at 600 ppb, with a NO content of 101 ppm (measured by N 2 dilution) and diluted to about 600 ppb by using a zero air generator. When the gas system reached adsorption-desorption equilibrium, the long arc xenon lamp was turned on and after 30 min, the long arc xenon lamp was turned off for 30 min. Chemiluminescent NO x The analyzer (Teledyne Technology, T200) continuously monitored the NO concentration in the reaction chamber under light / dark conditions (Guo et al., 2022). In addition, after the test, the powder was recovered and supplemented to 0.2 g for a secondary test to test the stability of the quantum dot-enhanced long afterglow synergistic photocatalytic material. Catalyst degradation rate:

[0032] AMHT photocatalytic degradation of formaldehyde: The degradation of formaldehyde by quantum dot enhanced long afterglow synergistic photocatalytic materials was determined by the 4-amino-3-hydrazine-5-mercapto-1,2,4-triazole (AHMT) method. First, 0.25 g AHMT was dissolved in 50 mL 0.1 mol / L hydrochloric acid solution. 1000 ul 50 mg / kg formaldehyde solution was dispersed in 5 mL aqueous solution, sprayed on qualitative filter paper, and dried. The quantum dot enhanced long afterglow synergistic photocatalytic material was dispersed on the surface of the filter paper and treated with light of different durations. After illumination, a mixture of 5 mol / L KOH and AHMT was dripped on the surface of the filter paper in turn, and the color of the filter paper was observed and recorded with a colorimeter.

[0033] Photocatalytic degradation of tetracycline: The photocatalytic activity of quantum dot-enhanced long afterglow synergistic photocatalytic materials was evaluated by the photocatalytic degradation reaction of tetracycline hydrochloride (TC) under visible light conditions. A 300 W xenon lamp (wavelength range: 320 nm ≤ λ ≤ 780 nm) was used as the light source, and a 420 nm cutoff filter was used to provide visible light irradiation. The monochromatic lamps had wavelengths of 365, 578, 630, and 940 nm, respectively. 100 mL of TC (10 mg / L) and 0.05 g of photocatalyst were added to a 250 mL beaker. Before illumination, the suspension was stirred continuously in the dark for 60 min until the adsorption-desorption equilibrium between TC and the photocatalyst was established. Every 5 min, 5 mL of the solution was collected and centrifuged at 8000 rpm for 5 min to remove the photocatalyst. The absorbance at 357 nm was then recorded using a UV-visible spectrophotometer to detect the concentration of TC.

[0034]

[0035] Photocatalytic degradation of organic dyes: Similarly, a 300 W xenon lamp (wavelength range: 320 nm ≤ λ ≤ 780 nm) was used as the light source, and a 420 nm cutoff filter was used to provide visible light irradiation. The wavelengths were 365, 578, 630, and 940 nm, respectively. 100 mL of methylene blue / rhodamine B (10 mg / L) and 0.05 g of photocatalyst were added to a 250 mL beaker. Before illumination, the suspension was stirred continuously in the dark for 60 min until the adsorption-desorption equilibrium between TC and the photocatalyst was established. Every 5 min, 5 mL of the solution was collected and centrifuged at 8000 rpm for 5 min to remove the photocatalyst. The absorbance at 357 nm was then recorded using a UV-visible spectrophotometer to detect the concentration of the organic dye.

[0036]

[0037] The experimental results of photocatalytic degradation of NO are shown in Table 1, and the test results of AMHT photocatalytic degradation of formaldehyde, tetracycline and organic dye color difference are shown in Table 2.

[0038] Table 1 NO degradation test under light / dark conditions

[0039] It can be seen from the test results in Table 1 that: by comparing Examples 1-4, it can be seen that increasing the urea, titanium dioxide and zinc oxide in the photocatalytic components can effectively improve the photocatalytic ability of the photocatalyst, and bismuth nitrate can be converted into bismuth-based oxygen-containing salts as the interface bonding material for the combination of quantum dots and long afterglow materials. Strontium aluminate and strontium silicate as long afterglow materials give the catalyst the ability to continue photocatalytic oxidation in a dark environment. Therefore, most samples have a significant hysteresis in the rebound of NO concentration after turning off the light source, and the concentration when the steady state is restored is less than the initial concentration. Urea, melamine, dicyandiamide, etc. are sources of carbon nitride of multiple sizes. Thanks to the protective effect of cyanuric acid, loose and porous carbon nitride nanosheets with multiple hierarchical structures are produced under the action of ammonium sulfate decomposition. This special structure gives the material better photocatalytic stability.

[0040] Table 2 Test results of AMHT, tetracycline and organic dyes

[0041] It can be seen from the test results in Table 1 that by comparing Examples 1-4, it can be seen that increasing the bismuth nitrate, urea, titanium dioxide and zinc oxide in the photocatalytic components can effectively improve the photocatalytic ability of the photocatalyst, which is not only reflected in the effective degradation of tetracycline and organic dyes by the material, but also in the oxidation of small molecule organic formaldehyde. The heterojunction constructed by bismuth tungstate, zinc oxide, titanium dioxide and multi-sized carbon nitride greatly improves the photocatalytic ability. In addition, multi-sized and multi-morphological carbon nitride also provides conditions for the formation of multi-material heterojunctions. The gain of quantum dots, strontium aluminate and strontium silicate on the catalytic activity of materials under illumination conditions is mainly reflected in the optimized interface structure, which is conducive to the further separation and migration of photogenerated carriers.

[0042] The above are preferred embodiments of the present invention. It should be pointed out that, for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as within the scope of protection of the present invention.

Claims

1. A method for preparing a quantum dot enhanced long afterglow synergistic photocatalytic material, characterized in that: The following steps are involved: S1. Dissolve bismuth nitrate in ethylene glycol, add strontium aluminate and strontium silicate successively, disperse evenly to obtain a quantum dot solution, and stir; Dissolve citric acid or ammonium citrate in water, add sodium tungstate and cuprous sulfide in turn, disperse evenly, stir to obtain a suspension; slowly add the suspension into the vigorously stirred quantum dot solution, stir to obtain solution A; The solution A is kept warm, then cooled, filtered, washed, and dried to obtain product A; S2. The urea, ammonium sulfate and cyanuric acid are dissolved in water, and dicyandiamide and melamine are added, and the mixture is evenly dispersed to obtain a solution B, and the water in the solution B is evaporated to obtain a solid, and the solid is annealed and sintered to obtain a product B; S3. Grind the nano-titanium dioxide, zinc oxide, the product A and the product B evenly, perform secondary annealing and sintering, and grind again into powder to obtain a composite material, namely, a quantum dot enhanced long afterglow synergistic photocatalytic material.

2. The method for preparing the quantum dot enhanced long afterglow synergistic photocatalytic material according to claim 1, characterized in that: The stirring time in S1 is 0.5-2h, the stirring speed is 500-700rpm; the intense stirring speed is 1000-1200rpm.

3. The method for preparing the quantum dot enhanced long afterglow synergistic photocatalytic material according to claim 1, characterized in that: The insulation condition of the solution A is 180-200° C. for 24-26 hours. After insulation, the solution A is cooled to room temperature and filtered. After filtration, the washing method is to wash with water and ethanol alternately for 2-3 times.

4. The method for preparing the quantum dot enhanced long afterglow synergistic photocatalytic material according to claim 1, characterized in that: The temperature at which the water of the solution B evaporates is 65-85°C.

5. The method for preparing the quantum dot enhanced long afterglow synergistic photocatalytic material according to claim 1, characterized in that: The solid annealing conditions are a temperature of 550-600° C. and a time of 2-3 hours; the solid annealing uses a muffle furnace.

6. The method for preparing the quantum dot enhanced long afterglow synergistic photocatalytic material according to claim 1, characterized in that: The grinding time is greater than 0.5h, and the grinding includes manual grinding and mechanical grinding.

7. The method for preparing the quantum dot enhanced long afterglow synergistic photocatalytic material according to claim 1, characterized in that: The dispersion is uniformly carried out by ultrasonic dispersion.

8. The method for preparing quantum dot enhanced long afterglow synergistic photocatalytic material according to claim 1, characterized in that: The bismuth nitrate and sodium tungstate are hydrates.

9. The method for preparing the quantum dot enhanced long afterglow synergistic photocatalytic material according to claim 1, characterized in that: The strontium aluminate and strontium silicate are sieved through a 300-mesh sieve.

10. A quantum dot enhanced long afterglow synergistic photocatalytic material as claimed in any one of claims 1 to 9, characterized in that: The invention comprises the following raw materials: a fluorescent component I and a photocatalytic material component II; The fluorescent component I comprises the following raw materials in parts by weight: 1-2 parts of citric acid or ammonium citrate, 2-3 parts of strontium aluminate, 2-3 parts of strontium silicate, 2-3 parts of sodium tungstate, 2-3 parts of bismuth nitrate, 2-3 parts of cuprous sulfide, 10-20 parts of water, and 40-45 parts of ethylene glycol; The photocatalytic material component II comprises the following raw materials in parts by weight: 2-3 parts of urea, 2-3 parts of ammonium sulfate, 2-3 parts of melamine, 2-4 parts of dicyandiamide, 2-3 parts of cyanuric acid, 2-3 parts of nano titanium dioxide, 2-3 parts of zinc oxide and 10-15 parts of water.